A study on technical analysis of s&p cnx nifty index - M, Ragupathi; B, Arthi (Journal of Management and Science, 2013)
Technical analysts do not attempt to measure a security's intrinsic value; instead they look at stock charts for patterns and indicators that will determine a stock's future performance. The use of past performance should come as no surprise. People using fundamental analysis have always looked at the past performance of companies by comparing fiscal data from previous quarters and years to determine future growth. The difference lies in the technical analyst's belief thatsecurities move according to very predictable trends and patterns. These trends continue until something happens to change the trend, and until this change occurs, price levels are predictable. There are many instances of investors successfully trading a security using only their knowledge of the security's chart, without even understanding what the company does. However, although technical analysis is a terrific tool, most agree it is much more effective when used in combination with fundamental analysis. The technical analysis reveals the peaks, bottoms, trends, patterns and other factors affecting a stock‘s price movement and then makes buy/sell decisions based on those factors. The tools namely RSI and EMA have been used to predict the index price movement of S&P CNX Nifty.